2021
DOI: 10.1038/s41598-021-81479-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of serum C-mannosyl tryptophan by novel assay to evaluate renal function and vascular complications in patients with type 2 diabetes

Abstract: C-Mannosyl tryptophan (CMW) is a unique glycosylated amino acid, and a candidate novel biomarker of renal function. In type 2 diabetes (T2D), a combination of metabolites including CMW has recently been the focus of novel biomarkers for the evaluation of renal function and prediction of its decline. However, previous quantification methods for serum CMW have several limitations. We recently established a novel assay for quantifying serum CMW. Serum CMW from 99 Japanese patients with T2D was quantified by this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…The 1 H NMR spectrum exhibited signals of an exchangeable proton (δ H 12.4, s), four protons attached to an aromatic moiety (δ H 7.20, 1H, m; δ H 7.21, 1H, m; δ H 7.48 and 7.82, d, J = 7.1), and protons of a sugar moiety (Table 1). The 13 C NMR spectrum showed nine sp 2 hybridized carbon signals (one ester carbon at δ C 162.6, four sp 2 tertiary hybridized carbons at δ C 112.7, 119.4, 121.9 and 122.8, four sp 2 quaternary hybridized carbons at δ C 100.0, 125.0, 136.9, and 147.2), and six sugar carbons (δ C 58.6, 60.5, 67.9, 69.5, 77.9, and 81.2) (Table 2). Heteronuclear multiple bond correlations (HMBCs) observed from NH-1 to C-2/C-3/C-4a/C-7a, from H-4 to C-3, and from H-7 to C-4a, together with the 1 H− 1 H correlated spectroscopy (COSY) correlation of H-4/H-5/H-6/H-7, confirmed the presence of an indole moiety.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1 H NMR spectrum exhibited signals of an exchangeable proton (δ H 12.4, s), four protons attached to an aromatic moiety (δ H 7.20, 1H, m; δ H 7.21, 1H, m; δ H 7.48 and 7.82, d, J = 7.1), and protons of a sugar moiety (Table 1). The 13 C NMR spectrum showed nine sp 2 hybridized carbon signals (one ester carbon at δ C 162.6, four sp 2 tertiary hybridized carbons at δ C 112.7, 119.4, 121.9 and 122.8, four sp 2 quaternary hybridized carbons at δ C 100.0, 125.0, 136.9, and 147.2), and six sugar carbons (δ C 58.6, 60.5, 67.9, 69.5, 77.9, and 81.2) (Table 2). Heteronuclear multiple bond correlations (HMBCs) observed from NH-1 to C-2/C-3/C-4a/C-7a, from H-4 to C-3, and from H-7 to C-4a, together with the 1 H− 1 H correlated spectroscopy (COSY) correlation of H-4/H-5/H-6/H-7, confirmed the presence of an indole moiety.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…C -Mannosyl tryptophan ( 5 ) was initially discovered in RNase2 from human urine and erythrocytes. , It was also found in marine ascidians and sponges and can be used as a promising biomarker candidate of renal function . Related compounds with potent cytotoxicities were reported from Radix isatidis , a traditional Chinese medicine Ban Lan Gen …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that higher urine C -Man-Trp levels were associated with a higher risk of adverse kidney events, such as kidney failure and acute kidney injury, and death [ 136 ]. We examined the level of serum C -Man-Trp in patients with type 2 diabetes, and found that the level of serum C -Man-Trp is significantly correlated with that of the creatinine or cystatin C, indicating that serum C -Man-Trp is useful to estimate the renal function in patients with type 2 diabetes [ 137 ]. It is also noteworthy that the level of serum glucose showed no correlation with that of serum C -Man-Trp of diabetic patients whose renal function is maintained (eGFR > 60 mL/min/1.73 m 2 ).…”
Section: Biomedical Topics Of Protein C -Mannosylation and C -Man-trpmentioning
confidence: 99%
“…In type 2 diabetic patients, the level of serum C -Man-Trp was increased with the progression of peripheral artery disease as assessed by ankle-brachial pressure index (ABI) [ 137 ]. This may be compatible with the fact that C -mannosylated TSP-1 was upregulated in aortic tissues of diabetic Zucker fatty rats [ 124 ].…”
Section: Biomedical Topics Of Protein C -Mannosylation and C -Man-trpmentioning
confidence: 99%